2016
DOI: 10.1186/s12900-016-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Human sex hormone-binding globulin as a potential target of alternate plasticizers: an in silico study

Abstract: BackgroundCurrently, alternate plasticizers are used to replace phthalate plasticizers in children’s toys, medical equipments and food packaging, due to the adverse effects of phthalate compounds on human health and laws prohibiting their use. Current information regarding the safety and potential adverse effects of alternate plasticizers is limited and recent studies have found alternate plasticizers to display similar characteristics to those observed in phthalate plasticizers. This study was undertaken to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…There is a significant lack of data on endocrine potency of these replacement phthalates. This highlights a need for further investigation especially as in silico results show they interfere with human sex hormone-binding globulin [ 66 ] and increase insulin resistance [ 67 ]. In 2002, the plasticizer 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH) was introduced in the European market as a substitute for DEHP.…”
Section: Discussion On Eds In Construction and Plastic Industry Tementioning
confidence: 99%
“…There is a significant lack of data on endocrine potency of these replacement phthalates. This highlights a need for further investigation especially as in silico results show they interfere with human sex hormone-binding globulin [ 66 ] and increase insulin resistance [ 67 ]. In 2002, the plasticizer 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH) was introduced in the European market as a substitute for DEHP.…”
Section: Discussion On Eds In Construction and Plastic Industry Tementioning
confidence: 99%
“…SHBG is hormone-related biomarker that has been reported to affect free-circulating hormone levels and represents a potential target for the phthalates endocrine disruptor function in the human body [ 56 ]. Phthalates have been suggested to have a potential disrupting activity in the endocrine homeostasis function of SHBG [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no endocrine disruption effect has been assessed with DINP metabolites, but recent data shows that the parent plasticizer (DINP) exhibits a binding affinity with SHBG in the in silico study of Sheikh et al [ 27 ], with a docking complex that forms 86% of interactions. Moreover, DINP exposure led to significant transcriptional changes even at low-exposure concentrations, suggesting a great endocrine disruption potency when tested in zebrafish in the work of Lee et al [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children’s exposure to DINCH should be investigated carefully as the total exposure may be close to the tolerable daily intake according to the National Industrial Chemicals Notification and Assessment Scheme (NICNAS) public report [ 26 ]. Moreover, Sheick et al [ 27 ] recently observed that DINCH showed high binding affinity with sex hormone binging globulin (SHBG), suggesting that the alternate plasticizer has potential to strongly inhibit the steroid binding function of SHBG. Therefore, it cannot be excluded that DINCH can cause a potential disruption effect on the androgen and estrogen homeostasis of SHBG and thus interfere with steroid signaling functions.…”
Section: Introductionmentioning
confidence: 99%